2016
DOI: 10.1016/j.jclepro.2016.06.095
|View full text |Cite
|
Sign up to set email alerts
|

A removal kinetics approach for evaluation of economic cleaning protocols for pink guava puree fouling deposit

Abstract: Cleaning-in-place is a common process in food industries to maintain the hygiene of the processing system. In this paper, analysis on removal kinetics of the fouling deposit has shown promising results which can be used to improve CIP protocol. The removal kinetics analyses on the cleanability experiments of pink guava puree fouling deposit were done using the laboratory-scale cleaning test rig. The experiments' parameters were temperatures (35-70 °C), Sodium hydroxide concentrations (1.0-2.0 wt%) and fluid ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…Purchasing commercial food-grade cleaning detergents can be a burden for SMEs. The cost of cleaning chemicals can contribute up to 58% of total cleaning costs [17]. The selection of affordable and durable electrode materials will minimize the maintenance cost for the electrolyzing unit.…”
Section: Selection Of Anode and Cathode Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Purchasing commercial food-grade cleaning detergents can be a burden for SMEs. The cost of cleaning chemicals can contribute up to 58% of total cleaning costs [17]. The selection of affordable and durable electrode materials will minimize the maintenance cost for the electrolyzing unit.…”
Section: Selection Of Anode and Cathode Materialsmentioning
confidence: 99%
“…There are three main types of chemicals used for the cleaning and disinfection process: alkaline (e.g., sodium hydroxide), acidic (e.g., nitric acid), and disinfectants (e.g., hydrogen peroxide, sodium hypochlorite) [15]. Carbohydrate-based fouling deposits such as pink guava puree fouling deposit [16][17][18] and chili sauce fouling deposit [19] are alkaline soluble. In contrast, mineral-based fouling deposits such as calcium are developed mostly from beer [20,21] and dairy [22][23][24] and are acid soluble [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cost of cleaning includes the cost of water, energy, chemical, wastewater treatment, and downtime. Cleaning chemical may affect the total cleaning cost greatly (Khalid et al, 2016). Studies performed by Khalid et al (2016) has shown that cleaning performed with a high concentration of 2.0 wt % of NaOH need almost extra $1400/m 2 of fouling deposit area, compared to cleaning performed without NaOH.…”
Section: Introductionmentioning
confidence: 99%
“…Cleaning chemical may affect the total cleaning cost greatly (Khalid et al, 2016). Studies performed by Khalid et al (2016) has shown that cleaning performed with a high concentration of 2.0 wt % of NaOH need almost extra $1400/m 2 of fouling deposit area, compared to cleaning performed without NaOH. When cleaning was performed without NaOH, the fouled stainless steel cannot reach 100% physically clean condition.…”
Section: Introductionmentioning
confidence: 99%